Characterization of CD4+ and CD8+ T cells responses in the mixed lymphocyte reaction by flow cytometry and single cell RNA sequencing - Mangelinck, Adèle; Dubuisson, Agathe; Becht, Etienne; Dromaint-Catesson, Sandra; Fasquel, Manon; Provost, Nicolas; Walas, Dawid; Darville, Hélène; Galizzi, Jean-Pierre; Lefebvre, Céline; Blanc, Véronique; Lombardi, Vincent (Frontiers in Immunology, 2024)
The Mixed Lymphocyte Reaction (MLR) consists in the allogenic co-culture of monocytes derived dendritic cells (MoDCs) with T cells from another donor. This in vitro assay is largely used for the assessment of immunotherapy compounds. Nevertheless, the phenotypic changes associated with lymphocyte responsiveness under MLR have never been thoroughly evaluated.Methods: Here, we used multiplex cytokine and chemokine assays, multiparametric flow cytometry and single cell RNA-sequencing to deeply characterize T cells activation and function in the context of CD4 + -and CD8 + -specific MLR kinetics.We showed that CD4 + and CD8 + T cells in MLR share common classical markers of response such as polyfunctionality, increased proliferation and CD25 expression but differ in their kinetics and amplitude of activation as well as their patterns of cytokines secretion and immune checkpoints expression. The analysis of immunoreactive Ki-67 + CD25 + T cells identified PBK, LRR1 and MYO1G as new potential markers of MLR response. Using cell-cell communication network inference and pathway analysis on single cell RNA-sequencing data, we also highlighted key components of the immunological synapse occurring between T cells and the stimulatory MoDCs together with downstream signaling pathways involved in CD4 + and CD8 + T cells activation.Conclusions: These results provide a deep understanding of the kinetics of the MLR assay for CD4 + or CD8 + T cells and may allow to better characterize compounds impacting MLR and eventually identify new strategies for immunotherapy in cancer.